Microfluidic systems as a novel approach for microalgal bioprocess - Karacaoglu, Beyza; Inan, Benan; Ozcimen, Didem Balkanli (ELSEVIER, 2023)
Challenges such as controlling parameters for microalgal bioprocess optimization, increased need for inoculum and chemicals with the increasing number of experiments, long procedures and high production costs make it difficult to commercialize high value-added bioactive compounds from microalgae. Furthermore, downstream processes comprise the majority of the total production costs and increase the amount of energy consumed, depending on the desired purity percentage and the biochemical features of the material. So, it is important to maximize the effectiveness, quality, and economic factors of both upstream and downstream processes. Due to their micro-scale size, diluted cultures and controlled operational parameters, reduced sample and material utilization, increased mass and heat transfer, better species interaction, and high-throughput cell/reagent pro-cessing capabilities, microfluidic devices are becoming increasingly used in microalgal bioprocess studies for both fundamental research and industrial applications. Additionally, microfluidic devices outperform conven-tional techniques in their capacity to carry out a lot of functions, including the separation and more sensitive analysis of small amounts of samples. In this review, diverse microfluidic platforms for microalgal cultivation, purification and separation processes, sorting and high-throughput screening of microalgae, and emerging studies of microfluidic technologies in various microalgal processes are discussed.
Keywords: Microfluidics; Microalgae; Bioprocess; Microchip; Biotechnology; HAEMATOCOCCUS-PLUVIALIS; SUSTAINABLE MICROALGAE; CELL-CULTURE; SEPARATION; EXTRACTION; ASTAXANTHIN; PLATFORM; CULTIVATION; BIOREACTOR; Biotechnology & Applied Microbiology; Engineering